Unintended Supplications In Prophetic Hadith: A Linguistic And Shariah Analysis - Md Din, Omar Bin; Tohyala, Ibrahim Wanni; Abdelfattah, Sami Samir; Mohammad Alramadeen, Mohammad Khalil; Ali Giyash, Mohammed Abdullah (Ijaz Arabi Journal of Arabic Learning, 2025)
The Prophetic Hadiths encompass a variety of expressions classified as supplications, yet they are not intended as prayers in their meaning and significance. These expressions belong to the linguistic traditions of the Arabs, forming part of their rhetorical and verbal styles that distinguished them from other nations. This research focuses on studying these eloquent Arabic styles as the Prophet articulated them, may Allah bless him and grant him peace, by examining their nature and connotations. It aims to clarify their true meaning and intent, explore the reasons for their usage, and analyse the variations in their meanings based on the contexts in which they appear. A precise linguistic analysis of these expressions will adhere to linguistic principles and rules. Furthermore, the study will examine scholars’ interpretations of these expressions, linking and comparing them with their Shariah significance. This includes determining the meanings these expressions conveyed within the framework of Islamic law and exploring the relationship between their linguistic and Shariah connotations. The key objectives of this research include clarifying certain linguistic styles that appear to contradict their literal meanings to highlight their deep-rooted Arabic origins. Establishing a connection between these linguistic origins and their Shariah implications demonstrates how they acquired legal and contextual meanings during the Islamic era. The study adopts a descriptive and analytical approach by linking the linguistic origins of unintended supplications with their Shariah meanings and analysing their interconnections. The research is expected to yield significant findings, primarily proving the importance of linking linguistic meanings with the technical contextual meanings in Shariah to accurately determine the true implications of Prophetic texts.